Recovery of gallium from wafer fabrication industry wastewaters by Desferrioxamine B and E using reversed-phase chromatography approach. (1st July 2019) - Jain, Rohan; Fan, Siyuan; Kaden, Peter; Tsushima, Satoru; Foerstendorf, Harald; Barthen, Robert; Lehmann, Falk; Pollmann, Katrin
Abstract: Gallium (Ga) is a critical element in developing renewable energy generation and energy efficient systems. The supply of Ga is at risk and needed recycling technologies for its availability in future. This study demonstrated the recovery of Ga 3+ from low gallium concentrated wafer fabrication industry wastewaters using the siderophores desferrioxamine B (DFOB) and desferrioxamine E (DFOE). The complexation of Ga 3+ by DFOB and DFOE was through hydroxamate group as demonstrated by infrared spectroscopy, nuclear magnetic resonance and density functional theory calculations. The high selectivity of DFOB/E towards Ga 3+ was observed due to the formation of highly stable complex. Indeed, due to the formation of such high stability complex, the DFOB and DFOE were able to successfully complex 100% Ga in the two different process water from wafer fabrication industry. For the recovery of the siderophores, a high rate of decomplexation of Ga (>90%) was achieved upon addition of 6 times excess of ethylenediaminetetraacetic acid (EDTA) at pH of 3.5. More than 95% of Ga-DFOB and Ga-DFOE complex were recovered with purity (% of Ga moles in comparison to total moles of metals) of 69.8 and 92.9%, respectively by application of a C18 reversed-phase chromatography column. This study, for the first time, demonstrated a technical solution to the recovery of Ga 3+ from the low concentrated wastewater based on siderophores and reversed-phase chromatography. A German patent application had been filed for this technology. Graphical abstract: Image 1 Highlights: DFOB and DFOE can selectively complex Ga 3+ from its low concentrated real wastewaters. Reversed-phase HPLC could recover more than 90% of Ga and regenerated DFOB/E. Ga purity in recovered Ga-DFOB and Ga-DFOE complexes was 69.8 and 92.9%.